Evaluación de la síntesis de una película bioplástica a escala laboratorio a partir de residuos de mango (Mangífera Índica) (2022)
The main objective of this degree work was to perform the synthesis of a bioplastic film through the extraction of starch obtained from mango residues, this being the raw material for the different formulations of the expected biopolymer. During the development of the objectives, different studies were taken into account in which various prototypes of bioplastic films were developed and, through these observed results, a quantitative method of empowerment and selection was established to find the optimal process to develop the expected bioplastic. In this way, when selecting the process with the best weighting, the main production stages were clear that would lead to an optimal obtainment of the starch used as raw material and, likewise, of the bioplastic film. The extraction and synthesis process was supported by a design of experiments, through which it was expected to find different formulations whose characteristics were comparable to those of conventional polymers. Thus, with a total of 18 types of biopolymer films, they are subjected to mechanical tests in order to find that the synthesized specimens would have common behaviors of fairly flexible polymers or elastomers, since they did not present failures against the application of the maximum force of the material. equipment used for this purpose.